Complex Considerations in Couples' Financial Information Management: Extending the Theory of Motivated Information Management. (April 2018) - Fowler, Craig; Gasiorek, Jessica; Afifi, Walid
Using Time 1 to Time 2 data from 387 adults, we examine the effectiveness of the theory of motivated information management (TMIM) in accounting for the various processes by which adults in committed romantic relationships manage financial uncertainty via communication with their partners. Our results indicate that the TMIM operates well in this context. We also contribute to the theoretical development of TMIM's revised theoretical framework in three ways, namely, by (a) examining the joint operation of positive and negative emotions (anxiety and optimism, respectively) on information management, (b) testing two types of outcome expectancies (knowledge and relationship), and (c) testing the model's prediction of multiple information management strategies (i.e., direct and indirect information seeking, avoidance, and cognitive reappraisal). Findings indicate that both (a) anxiety and optimism, and (b) knowledge outcome expectancies and relationship outcome expectancies differentially contributed to information management decisions.